DETERMINANTS OF CSR DISCLOSURE MODERATED BY THE ROLE OF GOOD CORPORATE GOVERNANCE - Setijaningsih, Herlin Tundjung; Kurniawan, Inneke (International Journal of Application on Economics and Business, 2023)
This study aims to analyze the effect of sales growth, profitability, and tax avoidance on CSR disclosure. This study also aims to analyze whether the role of gender diversity which is part of GCG strengthen the influence of each independent variable on CSR disclosure. This study used 72 observation obtained from 18 mining companies listed on Indonesian Stock Echange for period 2016-2019. The analytical techniques used are the multiple regression analysis and moderated regression analysis (MRA) on EViews 12. Research results show that sales growth has a positive effect on CSR disclosure, while profitability and tax avoidance have no effect on CSR disclosure. In addition, gender diversity is not able to strengthen the effect of sales growth, profitability, and tax avoidance on CSR disclosure.